Analisis Penilaian Kinerja Karyawan pada PT. La Vida Herculon - Setyadi, Rafly Agam; Sungkono, Sungkono (Journal of Economics and Management, 2023)
Performance appraisal of employees is one important aspect in human resource management within a company. An effective performance appraisal process can provide significant benefits, such as identifying employees' strengths and weaknesses and measuring individual contributions to company goals. PT La Vida Herculon has implemented employee performance appraisal as one instrument to measure employee performance. This study involves observation, interviews, and analysis of the existing performance appraisal process in the company. The research also refers to current theories and practices in human resource management and performance appraisal to support the analysis and recommendations presented. The hope is that this research can provide a deeper understanding of employee performance appraisal at PT La Vida Herculon and make a positive contribution to the development of a more effective and relevant performance appraisal system aligned with the company's needs. With an increased understanding of the importance of effective performance appraisal, PT La Vida Herculon can create a more productive work environment, motivate employees to develop, and enhance overall company goal achievement. Through this research, it is expected to provide useful information for PT La Vida Herculon in improving the employee performance appraisal system and achieving competitive advantage in this increasingly competitive industry.